Adsorptive Behavior of Methylene Blue onto Sawdust of Sour Lemon, Date Palm, and Eucalyptus as Agricultural Wastes. Issue 7 (3rd July 2019) - Esmaeili, Hossein; Foroutan, Rauf
Abstract: In the present study, to remove methylene blue (MB) from aqueous solution, some agricultural residues and cheap bioadsorbents such as sawdust of palm trees, eucalyptus, and sour lemon were used. To do this, significant parameters like contact time, temperature, pH, initial concentration, and adsorbent dosage were checked. The results affirmed that the best conditions for MB adsorption from aqueous solution were obtained such as the temperature of 25 °C, pH of 8, adsorbent dosage of 2g/L, contact time of 120 minutes, and dye concentration of 5 mg/l which under these conditions the adsorption efficiencies determined were 95.8, 93.4, and 92.8% using sawdust of palm tree, eucalyptus, and sour lemon, respectively. Also, the equilibrium behavior of adsorbents showed that the Freundlich model could better predict the adsorption behavior of the process due to having a larger correlation coefficient ( R 2 ). The maximum biosorption capacities by Langmuir isotherm model were also obtained 54, 53.5, and 52.4 mg/g for sawdust of palm trees, eucalyptus, and lemon, respectively, which were significant amounts. In addition, kinetic behavior of adsorption showed that pseudo-second-order model can describe the kinetics of the adsorption process better than the pseudo-first-order model. Moreover, kinetic, equilibrium, and thermodynamic behaviors of adsorption affirmed that the biosorption process was desirable, physisorption, spontaneous, and exothermic. Graphical Abstract: uf0001